Analysis of the Influence of System Quality, Information Quality, and Service Quality on User Satisfaction Mobile Banking Users - Budi Prasetya; Dimas Prayogo (Publikasi Indonesia, 2025)
Mobile banking is one of the banking services that is integral to everyone's daily activities. However, sometimes its use experiences various obstacles, whether it is from the system, service, or information. This study aims to analyze the effect of system quality, information quality, and service quality on mobile banking user satisfaction. Using a quantitative approach and survey design, this study collected data through questionnaires distributed to mobile banking users. Regression analysis was used to identify the relationship and impact of each factor on user satisfaction. The results showed that system quality, information quality, and service quality have a significant influence on the level of user satisfaction. The findings emphasize the importance for banks to focus on continuous improvement in these aspects to enhance user experience and ensure high customer loyalty. This research provides valuable insights for the banking industry in designing more effective strategies to optimize mobile banking services.